Clinical Chronobiology: Circadian Rhythms in Health and Disease - Tomatsu, Shizuka; Abbott, Sabra M.; Attarian, Hrayr (Seminars in Neurology, 2025)
Circadian rhythms (CRs) are entrainable endogenous rhythms that respond to external stimuli and regulate physiological functions. The suprachiasmatic nucleus (SCN) in the hypothalamus is the mammalian master clock that synchronizes all other tissue-specific peripheral clocks, primarily through gamma-aminobutyric acid (GABA) and vasoactive intestinal polypeptide (VIP). The SCN follows Earth's 24-hour cycle by light entrainment through the retinohypothalamic tract. At the cellular level, the core clock genes CLOCK, BMAL1, PER1–PER3, CRY1, and CRY2 regulate CRs in a negative feedback loop. The circadian disruption of the sleep–wake cycle manifests in at least six distinct clinical conditions. These are the circadian rhythm sleep–wake disorders (CRSWDs). Their diagnosis is made by history, sleep diaries, and actigraphy. Treatment involves a combination of timed light exposure, melatonin/melatonin agonists, and behavioral interventions. In addition, CR disturbances and subsequent misalignment can increase the risk of a variety of illnesses. These include infertility and menstrual irregularities as well as diabetes, obesity, fatty liver disease, and other metabolic syndromes. In addition, a disruption in the gut microbiome creates a proinflammatory environment. CR disturbances increase the risk for mood disorders, hence the utility of light-based therapies in depression. People with neurodegenerative disorders demonstrate significant disturbances in their CRs, and in their sleep–wake cycles. Circadian realignment therapies can also help decrease the symptomatic burden of these disorders. Certain epilepsy syndromes, such as juvenile myoclonic epilepsy (JME), have a circadian pattern of seizures. Circadian disturbances in epilepsy can be both the consequence and cause for breakthrough seizures. The immune system has its own CR. Disturbances in these due to shift work, for instance, can increase the risk of infections. CR disturbances can also increase the risk of cancer by impacting DNA repair, apoptosis, immune surveillance, and cell cycle regulation. Moreover, the timing of chemotherapeutic agents has been shown to increase their therapeutic impact in certain cancers.
Keywords: circadian rhythms; circadian rhythm sleep–wake disorders; chronobiology; suprachiasmatic nucleus; CLOCK genes; metabolism; mood disorders; immune disturbances; neurodegeneration; cancer; epilepsy